Novosti . Novosti . News . Новости - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Chronicle of the revolt in Moscow; the work of a Moscow city hospital on helping the wounded; notification about the death of the French journalist Ivan Skopan and Russian servicemen during the revolt in Moscow; interruption of printing several periodical publications; coverage of the Moscow Revolt by foreign TV-companies; personnel reshuffle in the Russian government. Featured in the program: Havel, Václav (President of the Czech Republic); Aushev, Ruslan Sultanovich (President of Ingushetia); Grachev, Pavel Sergeevich (Defense Minister of the Russian Federation) Contributors: Mishina, Irina (Anchor) Хроника мятежа в Москве; работа московской городской больницы по помощи раненым; сообщение о гибели французского журналиста Ивана Скопана и российских военнослужащих в ходе мятежа в Москве; приостановление деятельности нескольких печатных изданий; освещение мятежа в Москве иностранными телекомпаниями; кадровые перестановки в российском правительстве. В программе участвуют: Гавел, Вацлав (Президент Чехии); Аушев, Руслан Султанович (Президент Ингушетии); Грачев, Павел Сергеевич (Министр обороны Российской Федерации) Создатели: Мишина, Ирина (Ведущий/Ведущая)